Spatial variability of soil roughness in persimmon plantations: A new combined ISUM (improved stock unearthing method) approach - da Silva, Alexandre Marco; Moradi, Ehsan; Rodrigo-Comino, Jesús; Cerdà, Artemi (Elsevier, 2019)
Soil roughness (SR) is an ecological indicator that describes the distribution of soil surface accumulations and ponds in a terrain, which allows understanding the connectivity of the flows as they act as sinks and sources of water and sediments. There is a set of methods that allows investigating the SR, and we test the use of the improved stock unearthing method (ISUM) as an easy-to-apply and low-cost approach. The ISUM has been initially tested in vineyards using the graft union and measures in the inter-row areas to assess the current soil surface level and estimate soil mobilization. In this research, we present an innovative application of ISUM for persimmons plantations (Diospyros kaki Linn.) to further analyze the microtopographical changes. We chose a persimmon plantation because of the existence of grafted parts in such species, which is a common characteristic in other plantations such as vineyards. To achieve this goal, we calculated the Roughness Index (RI) and the Transect Length Index (TLI) using the dataset generated by means of ISUM. The study was conducted in a conventional persimmon plantation in Eastern Spain. We performed a total of 2130 measures in an experimental plot of 490 m2 taking measures in each paired-plant with intervals of 100 mm. We detected that the studied area is predominantly slightly depressed (occurrence of this category in 69% of the plot) and the soil surface of the studied area presented in 95.5% of the studied area a pattern of roughness characterized as random-oriented. We argue that the ISUM was successfully employed also in a persimmons plantation because of the botanic characteristics of the trees that allowed us creating a feasible database generated to assess soil roughness and mobilization. Hence, we conclude that the ISUM is a method that can provide alternatives of analysis of soil roughness to allow including improvements in actions of restoration or conservation in cultivated soils.
Keywords: Agricultural management systems; Microtopographic analysis; Soil consolidation; Soil surface analysis